2021
DOI: 10.3390/su13126589
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Sexual Harassment Studies with Text Mining

Abstract: Sexual harassment has been the topic of thousands of research articles in the 20th and 21st centuries. Several review papers have been developed to synthesize the literature about sexual harassment. While traditional literature review studies provide valuable insights, these studies have some limitations including analyzing a limited number of papers, being time-consuming and labor-intensive, focusing on a few topics, and lacking temporal trend analysis. To address these limitations, this paper employs both co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 160 publications
0
16
0
1
Order By: Relevance
“…It is easier to express misogynistic attitudes and malicious emotions through social media than through face-to-face interaction. The #MeToo and #TimesUp campaigns highlight how individuals are using new technologies to connect with other survivors of sexual assault and share their stories on social media [ 87 ]; as a result, social media provides us with more access to content that discriminates against women. Due to the potential delicacy of the Chinese language, it is difficult to identify misogynistic content automatically.…”
Section: Further Discussionmentioning
confidence: 99%
“…It is easier to express misogynistic attitudes and malicious emotions through social media than through face-to-face interaction. The #MeToo and #TimesUp campaigns highlight how individuals are using new technologies to connect with other survivors of sexual assault and share their stories on social media [ 87 ]; as a result, social media provides us with more access to content that discriminates against women. Due to the potential delicacy of the Chinese language, it is difficult to identify misogynistic content automatically.…”
Section: Further Discussionmentioning
confidence: 99%
“…A few studies on sexual harassment adopted the systematic literature review (SLR) method. Karami et al (2021) reported that the work environment was one of the popular themes raised. The most vulnerable are people with disabilities or those suffering from chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies on sexual harassment adopted the systematic literature review (SLR) method. Karami et al. (2021) reported that the work environment was one of the popular themes raised.…”
Section: Introductionmentioning
confidence: 99%
“…This includes verbal or physical conduct, or any gesture of a sexual nature, particularly behavior construed as offensive or intimidating to the person concerned. Sexual harassment is one of the forms of sexual violence that has traditionally been most studied [13]. This interest has been boosted in recent years motivated, in part, by the media impact and social repercussions of specific acts, such as the accounts of sexual harassment given by victims themselves arising from viral phenomena such as #MeToo [14,15].…”
Section: Of 17mentioning
confidence: 99%